Mechanical performance and failure mechanism of U-steel support structure under blast loading - Zhao, Jin-Shuai; Yang, Jia-Hao; Li, Peng-Xiang; Zhu, Xin-Hao; Chen, Chong-Feng; Zhang, Jian-Cong (Frontiers in Earth Science, 2024)
The U-steel support structures of underground caverns are prone to instability and failure under blast loads. The purpose of the underground cavern reinforcement is to mobilise the self-supporting capacity of the surrounding rock to resist the blast. To better understand the mechanical performance and failure mechanism of the U-steel support, the fracture process and vibration behaviour of the support structure under blast loading are investigated by the microseismic monitoring experiment. The dynamic responses of the cavern support structures under blast loading are investigated, and the potentially hazardous sections of the U-steel support structure are revealed by the theoretical analysis. The microseismic monitoring results show that the blast induced microseismic events are concentrated in the arch shoulder of the small chainage, correspondingly the U-steel structures in this region have been partially extruded and deformed. The failure mechanism of the supporting structure is presented. In order to effectively inhibit the internal fracture evolution or macroscopic failure of the rock mass, the synergetic reinforcement scheme of the structures is proposed. The results of the research can be used as a reference for the design and control method of the U-steel support in similar projects.